2014
DOI: 10.1001/jamasurg.2014.73
|View full text |Cite
|
Sign up to set email alerts
|

Determining Whether Excision of All Fibroepithelial Lesions of the Breast Is Needed to Exclude Phyllodes Tumor

Abstract: Fibroepithelial lesions (FELs) are a common histologic finding on core needle biopsy (CNB) of the breast. Fibroepithelial lesions include fibroadenoma and phyllodes tumor, which can be difficult to distinguish with an initial CNB. An institutional experience was reviewed from February 12, 2001, to January 4, 2007, to determine the safety of selective rather than routine excision of FELs and to determine the factors associated with upgrading diagnosis of FELs to phyllodes tumors without definitive phyllodes tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
29
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 13 publications
(27 reference statements)
4
29
1
1
Order By: Relevance
“…The data available in literature on Phyllodes tumours include retrospective reviews and large, single-centre studies. [5][6][7][8][9] The following points summarize what these studies tell us about the management of Phyllodes tumours: • Prognosis is excellent for Phyllodes tumours following surgical excision, with no requirement for adjuvant therapy. 5,6 • As long as the microscopic surgical margins are free of disease, the extent of surgery does not correlate with disease-free survival or local recurrence.…”
Section: What Does the Literature Tell Us?mentioning
confidence: 99%
See 1 more Smart Citation
“…The data available in literature on Phyllodes tumours include retrospective reviews and large, single-centre studies. [5][6][7][8][9] The following points summarize what these studies tell us about the management of Phyllodes tumours: • Prognosis is excellent for Phyllodes tumours following surgical excision, with no requirement for adjuvant therapy. 5,6 • As long as the microscopic surgical margins are free of disease, the extent of surgery does not correlate with disease-free survival or local recurrence.…”
Section: What Does the Literature Tell Us?mentioning
confidence: 99%
“…5 • The upgrade rate of fibroepithelial lesions to Phyllodes tumours following a period of observation is low. 9 We performed a retrospective review at our single tertiary referral centre of all patients who had undergone surgical therapy for Phyllodes Phyllodes breast tumours are fairly uncommon, and they can be benign, borderline or malignant. General surgeons usually encounter them following the surgical excision of a breast lump that had the appearance of a fibroepithelial lesion.…”
Section: What Does the Literature Tell Us?mentioning
confidence: 99%
“…However, excision of such lesions—be it via open excision or vacuum‐assisted core needle biopsy—is not without risk including surgical or anesthetic complications, tissue distortion with unsatisfactory cosmetic result, and potential placement of unnecessary burden on limited health service resources. Large series have concluded that FA diagnosed by core needle biopsy with imaging pathologic concordance can usually be safely managed without further intervention and have advocated an individual case‐based approach toward management . Conversely, the potential of increasing morbidity and mortality with delayed diagnosis of higher grade disease is potentially catastrophic.…”
Section: Introductionmentioning
confidence: 99%
“…At present, despite many useful histologic pointers, there are no absolutely determinative features to distinguish between FA and benign PT on CNB resulting in a high number of excisions to outrule this lesion . The distinction between FA and PT in particular malignant PT is clinically important.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study of 313 biphasic neoplasms on core needle biopsy, only 1 (0.3%) was upgraded to malignant phyllodes at surgical excision. 38 Of the 59 patients with biphasic neoplasms who opted for surgical excision in our study cohort, 18 (30.5%) were found to have low-grade phyllodes tumors. These results are also similar to other studies, which have reported low-grade phyllodes tumor in 18.8% of 213 surgically excised lesions 39 and 30.2% of 43 surgically excised lesions.…”
Section: Discussionmentioning
confidence: 84%